Exploring Factors Influencing Advanced Practice Nurse Implementation: A Comparative Cross-Sectional Study in Seven European Countries - Van Hecke, Ann; Casey, Mary; Decoene, Elsie; Goossens, Godelieve A; Jokiniemi, Krista; Von Der Lühe, Verena; Köpke, Sascha; Morales-Asencio, José Miguel; Gutiérrez-Rodríguez, Laura del Carmen; Kort-Kristofersson, Gisli; Kinnaer, Lise-Marie; Wynendaele, Herlinde (Wiley, 2025)
Aim To investigate factors influencing the implementation of advanced practice nursing roles within healthcare organisations in seven European countries from the perspective of advanced practice nurses. Design A cross-sectional survey was conducted between September 2021 and December 2022, involving advanced practice nurses from Belgium, Finland, Germany, Iceland, Ireland, Spain and the Netherlands. The countries were selected to represent different stages of implementing advanced practice nursing roles, from emerging to well-established. Methods A self-administered questionnaire was used to address five domains: patient care, practice patterns, policy and legal, educational and workforce-related factors. Descriptive statistics, chi-squared tests and correspondence analysis were employed to identify patterns and country-specific differences across these domains of implementation factors.
https://openpolicyfinder.jisc.ac.uk/id/publication/7035
Keywords: Enfermería - Práctica; Cuidados de enfermería; Advanced practice; Clinical nurse specialist; Nurse practitioners; Policy; Quantitative approaches; Research implementation; Workforce issues